2018
DOI: 10.15835/nbha46211061
|View full text |Cite
|
Sign up to set email alerts
|

Pigments, Polyphenols and Antioxidant Activity of Leaf Extracts from Four Wild Rose Species Grown in Sicily

Abstract: Leaf methanolic extracts of four wild Rose species (Rosa canina L., R. corymbifera Borkh., R. micrantha Borrer ex Sm and R. sempervirens L.) grown in Sicily were analysed in order to evaluate differences among indigenous roses which could be used such as source of bioactive compounds and natural antioxidants. Leaves were harvested during two different periods (June and October) and their morphological characteristics were described. Leaf content of chlorophylls, total anthocyanins, total flavonoids, total poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
(47 reference statements)
5
23
1
Order By: Relevance
“…According to Bitis et al ., R. sempervirens leaves showed considerable high radical‐scavenging effect (DPPH and TEAC) by their EtOAc extracts. D'angiolillo et al . found that the radical scavenging activity of Rosa leaf extracts as evaluated by DPPH test, was affected by species variation and harvest period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bitis et al ., R. sempervirens leaves showed considerable high radical‐scavenging effect (DPPH and TEAC) by their EtOAc extracts. D'angiolillo et al . found that the radical scavenging activity of Rosa leaf extracts as evaluated by DPPH test, was affected by species variation and harvest period.…”
Section: Resultsmentioning
confidence: 99%
“…found that the radical scavenging activity of Rosa leaf extracts as evaluated by DPPH test, was affected by species variation and harvest period. In this report, R. canina leaf extracts were compared to three other roses ( R. corymbifera , R. micrantha and R. sempervirens ) and demonstrated to exhibit the highest DPPH radical scavenging ability when harvested in June and the lowest power when collected in October. As reported in a recent study and in contrast to our results with stems, the antioxidant ability of rose hip extracts of R. sempervirens measured by ORAC assay, was significantly more important (4576.77 μmol TE/g DE) than that recorded for R. canina (4493.64 μmol TE/g DE), R. micrantha (3761.11 μmol TE/g DE) and R. corymbifera (2726.68 μmol TE/g DE).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there was a significant increase in the content of chlorophyll a, chlorophyll b, and carotenoids (Figure 1). Carotenoids, in addition to being active as light-harvesting pigments [55,56], act as a scavenger of singlet oxygen species and quench the triplet state of chlorophyll molecules [57]. Under abiotic stress, cellular homeostasis is disrupted, leading to the production of free radicals, which in turn can result in oxidative damage [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a significant increase in the content of chlorophyll a, chlorophyll b, and carotenoids ( Figure 1 ). Carotenoids, in addition to being active as light-harvesting pigments [ 55 , 56 ], act as a scavenger of singlet oxygen species and quench the triplet state of chlorophyll molecules [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, rose possesses cosmetic and skin-moisturizing properties, can help reduce pain, functions as an aromatic deodorant, and invigorates the spleen. Its medicinal value is extremely high [16][17][18]. It is therefore worthwhile to explore the diversity and function of rose endophytic bacteria because they affect the functional properties of the roses themselves.…”
Section: Introductionmentioning
confidence: 99%